Penggunaan bahasa isyarat dalam perundangan Islam - Jasni Sulong, (Penerbit Universiti Kebangsaan Malaysia, 2007)

(untitled)
Sign language is a language that uses manual communication, body language and lip patterns instead of sound to convey meaning or message. It is commonly developed in deaf communities, which can include interpreters, friends and families of deaf people as well as the deaf and those who have hearing difficulties. Beside this disability, some normal people also know this language and use it in their communication. In this case, this paper is primarily intended to elaborate the significance of sign language in Islamic law as an evidence and witness for the deaf as well as normal people. The discourse is also trigerred on how far the law accepts sign language in order to give justice to both parties, especially in our present day courts